Analisis Target Laba Dalam Memaksimalkan Laba Umkm Alvo Archery Kota Sukabumi - Desti Karimah; Acep Samsudin; Dicky Jhoansyah (IPM2KPE, 2019)
This study aims to implement a profit target analysis at the Alvo Archery UKM so that the planned profit target is achieved. This study uses the method of observation and direct interviews with UKM Alvo Archery to obtain the required data. Research Results, Alvo Archery MSMEs must sell products: 108 horse bow units, 131 units of Batman, 95 units of brave units, 159 units of Adult units, Elegant Kids with 396 units, Adult Street Fighter with 193 units, Street Fighter Kids with 173 units, 143 units of elegant long bow, 128 units of Mindful, 157 units of Extreme, 128 units of Fight Black, 157 units of KZN 117, 1299 Arrows of Alvo Fiber, 2320 units of Arrow Bambu Sponge, 2320 Arrow Ramin Sponge unit, Target Board 50x50x5 as many as 773, Target Board 100x100x5 as many as 286 units. Conclusion, based on the above data, then Alvo Archery MSMEs must make profit planning in advance so that the desired profit can be achieved. From the results of the above calculations, Alvo Archery MSMEs must sell their products as much as calculated above so that the planned profits are achieved and get the maximum profit. Keywords: Target Profit, Profit, UMKM